1992
DOI: 10.1016/0020-7292(92)90278-q
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up of women with borderline cervical smear test results: Effects of age and viral infection on progression to high grade dyskaryosis

Abstract: Objective-To follow up and assess the significance of borderline change in cervical smears. Design-Retrospective study of women undergoing routine cervical cytological screening in 1981. Setting-Avon Cervical Screening Programme, covering 250 000 women in Bristol and Weston super Mare. Subjects-437 women showing borderline cervical changes in 1981 and 437 age matched controls with normal results in 1981. Main outcome measures-Cytological progression to high grade dyskaryosis (cervical intraepithelial neoplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In the current study, the few cases referred with ASCUS means that conclusions on the management of these patients cannot be drawn; there has been significant debate within the literature on this subject with up to 16% of patients progressing to CIN within 2 years 29,30 and 6–7% of cases already have high‐grade change 25,26 . The ASCUS LSIL Triage Study (ALTS) study has found that reflex HPV‐DNA testing is a useful option under these circumstances 31…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, the few cases referred with ASCUS means that conclusions on the management of these patients cannot be drawn; there has been significant debate within the literature on this subject with up to 16% of patients progressing to CIN within 2 years 29,30 and 6–7% of cases already have high‐grade change 25,26 . The ASCUS LSIL Triage Study (ALTS) study has found that reflex HPV‐DNA testing is a useful option under these circumstances 31…”
Section: Discussionmentioning
confidence: 92%
“…Hirschowitz et al found that 22.4% of women with borderline cytological changes had a smear test showing high grade dyskaryosis which developed between 13 and 106 months after the index smear. 1 Fifty per cent of these women, or 11.2% of their total study group, developed their high grade lesion within 34 months. The frequency with which a high grade lesion was identified after a borderline smear was therefore similar in the two studies.…”
Section: Discussionmentioning
confidence: 94%
“…1 More recently the British Society for Clinical Cytology and the Royal College of Pathologists cooperated to produce a series of guidelines defining borderline nuclear changes in cervical smears and provided illustrations to assist in their identification. 2 The appropriateness of these guidelines has been discussed publicly.…”
mentioning
confidence: 99%
“…9,12,15 One study included only women with borderline results,11 one study included both mild and moderate dyskaryosis but did not indicate the proportion of subjects with mild disease,10 and the last study included borderline results (30%), mild dyskaryosis (64%), and moderate dyskaryosis (6%). There seems to be no correlation between the scope of the inclusion criteria and the incidence of invasive disease.…”
Section: Resultsmentioning
confidence: 99%